Needs Analysis of the Development of Self-Directed Learning E-Module for the Scientific Writing Course - Sholeha, Monita (South Sulawesi Education Development (SSED), 2026)
The integration of course guidelines with learning materials hinders students’ comprehension and fosters dependence on tutors. Needs analysis, as the initial step in e-module development, is essential to identify students’ limitations and requirements. Employing Borg and Gall’s needs analysis model, this study gathered data through observation, questionnaires, and interviews with 30 students, and analysed the data both quantitatively and qualitatively. Results reveal the current guidebook excels in user-friendliness (98.23%), adaptability (94.70%), and self-containment (77.17%), but is merely adequate in stand-alone (68.47%) and self-instruction (61.43%) aspects. Therefore, an e-module equipped with examples, editable templates, self-quizzes with feedback, and tutorial videos is required.